Molecular cytogenetic characterization of de novo concomitant proximal 21q deletion of 21q11.2q21.3 and distal Xp deletion of Xp22.33p22.2 due to an unbalanced X;21 translocation detected by amniocentesis - Chih-Ping Chen; Shin-Wen Chen; Chao-Yun Wu; Schu-Rern Chern; Fang-Tzu Wu; Yen-Ting Pan; Peih-Shan Wu; Chen-Chi Lee; Li-Feng Chen; Wayseen Wang (Elsevier, 2023)
Objective: We present molecular cytogenetic characterization of de novo concomitant proximal 21q deletion of 21q11.2q21.3 and distal Xp deletion of Xp22.33p22.2 due to an unbalanced X; 21 translocation detected by amniocentesis. Case report: A 35-year-old, primigravid woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 45,X,der(X)t(X; 21) (p22.2; q21.3),-21. Simultaneous array comparative genomic hybridization (aCGH) revealed the result of an 11.9-Mb Xp22.33p22.2 deletion encompassing HCCS, SHOX, AMELX and OFD1 and a 15.4-Mb 21q11.2q21.3 deletion encompassing NRIP1 and APP. The pregnancy was subsequently terminated, and a malformed fetus was delivered with craniofacial dysmorphism. The parental karyotypes were normal. Polymorphic DNA marker analysis by quantitative fluorescence polymerase chain reaction (QF-PCR) confirmed a paternal origin of the 21q proximal deletion. Cytogenetic analysis of cord blood confirmed the karyotype of 45,X,der(X)t(X; 21) (p22.2; q21.3),-21. aCGH analysis of the cord blood confirmed the prenatal diagnosis. Conclusion: QF-PCR analysis is useful for determination of the parental origin of a de novo unbalanced X; autosome translocation detected by prenatal diagnosis. The information acquired is useful for genetic counseling under such a circumstance.